Nilai-Nilai dalam Tradisi Mabbarazanji - Iqbaliqbal, Iqbaliqbal; Rahmat,; Rahim, Abdul (Rihlah: Jurnal Sejarah dan Kebudayaan, 2023)
This research explains about the Mabbarazanji Tradition, Barzanji is a complement to the traditional ceremony or thanksgiving they do. Because without carrying out the barzanji at a traditional event, it is said that the ceremony is not perfect. The barzanji tradition is performed for various events (rituals) such as weddings, maulid, aqiqah and so on. This research focused on the background of the existence of the Barzanji Tradition in Parigi Village, Tinggimoncong District, Gowa Regency. The results of the study will show that the background of the existence of the Barzanji Tradition in Parigi Village is inseparable from the role of Sayyid Jalaluddin in Cikoang in welcoming the Prophet's birthday tradition (Maudu' Lompoa) in this tradition, the book by the Sayyid is read together, namely the book known as the A Rate (Assikkiri) manuscript. This manuscript is then read in every Aqikah ceremony, marriage and house entry.